2011
DOI: 10.1186/1471-2318-11-70
|View full text |Cite
|
Sign up to set email alerts
|

Use of CNS medications and cognitive decline in the aged: a longitudinal population-based study

Abstract: BackgroundPrevious studies have found associations between the use of central nervous system medication and the risk of cognitive decline in the aged. Our aim was to assess whether the use of a single central nervous system (CNS) medication and, on the other hand, the combined use of multiple CNS medications over time are related to the risk of cognitive decline in an older (≥ 65 yrs) population that is cognitively intact at baseline.MethodsWe conducted a longitudinal population-based study of cognitively inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…39 Moreover, a recent meta-analysis showed that opioids also increase the risk of delirium. 40 Meperidine was associated with the greatest risk of delirium, which is not surprising given its renally-cleared neurotoxic metabolite.…”
Section: Age-related Pharmacokinetic and Pharmacodynamic Changes And Rmentioning
confidence: 99%
“…39 Moreover, a recent meta-analysis showed that opioids also increase the risk of delirium. 40 Meperidine was associated with the greatest risk of delirium, which is not surprising given its renally-cleared neurotoxic metabolite.…”
Section: Age-related Pharmacokinetic and Pharmacodynamic Changes And Rmentioning
confidence: 99%
“…In contrast, in a prospective longitudinal study of 37 CNP patients on LTOT, cognitive performance (working memory, spatial span, and processing speed) were deficient when compared to both non‐opioid treated CNP patients and healthy controls . Similarly, a longitudinal analysis of 1,196 cognitively intact older adults with CNP observed cognitive decline on the Mini Mental State Examination (MSE) associated with LTOT or combined opioid and benzodiazepine use over a 7‐year duration, compared to healthy controls . A systematic review of 13 studies demonstrated varied results, with four studies showing improvements or stable cognitive functioning associated with LTOT (e.g., information processing, memory, attention, and psychomotor speed) and 4 studies demonstrating deficits (e.g., working memory, attention, and psychomotor speed) among LTOT patients versus nonopioid treated CNP patients and healthy controls .…”
Section: Phenomenologymentioning
confidence: 99%
“…11,14,15 Observational studies suggest there is considerable interpatient variability in tolerability and opioid-related adverse drug events (ADEs) vary according to the specific agent. 12,16,17 When used among older people, opioids have been associated with abuse, overdose, falls and fractures, 18e21 hospitalizations, 20 cognitive decline, 22,23 and delirium. 24 The use of opioids at the population level has increased substantially over the past decade 25e27 ; however, less is known about the change in opioid prevalence among institutionalized older people.…”
mentioning
confidence: 99%